Thermal Rectification and Thermal Logic Gates in Graded Alloy Semiconductors - Ryan C. Ng; Alejandro Castro-Alvarez; Clivia M. Sotomayor-Torres; Emigdio Chávez-Ángel (Energies, 2022)
Classical thermal rectification arises from the contact between two dissimilar bulk materials, each with a thermal conductivity (k) with a different temperature dependence. Here, we study thermal rectification in a Si(1−x)Gex alloy with a spatial dependence on the atomic composition. Rectification factors (R = kmax/kmin) of up to 3.41 were found. We also demonstrate the suitability of such an alloy for logic gates using a thermal AND gate as an example by controlling the thermal conductivity profile via the alloy composition. This system is readily extendable to other alloys, since it only depends on the effective thermal conductivity. These thermal devices are inherently advantageous alternatives to their electric counterparts, as they may be able to take advantage of otherwise undesired waste heat in the surroundings. Furthermore, the demonstration of logic operations is a step towards thermal computation.